Análisis cuantitativo del comportamiento del mercado de acceso banda ancha al servicio de internet residencial en Colombia, visto desde la dinámica de sistemas. Versión 0.1 (2019)
The System Dynamics is emerging as an alternative to the traditional techniques ofinformation analysis, since it permits analyze and synthesize different structural causesthat promote the behavior of interest. However, this involves raising awareness on therole of each element and how different actions carried out on parts of it, accentuate orattenuate the trend implicit in it (Garcia, 2007).Taking this aspects Into consideration, this article presents the first version of the modelto be developed within the research project "Model Market Access to BroadbandInternet Service to Residential, an Approach from the System Dynamics", in which thedifferent elements present in the market will be considered, and a simulation of theirbehavior will be conducted, using the Vensim PLE version 5.8c (2007) software,designed to work under the focus of system dynamics.